The use of varenicline to treat nicotine dependence among patients with cancer. Issue 10 (24th May 2016) - Price, Sarah; Hitsman, Brian; Veluz‐Wilkins, Anna; Blazekovic, Sonja; Brubaker, Tarah R.; Leone, Frank; Hole, Anita; Wileyto, E. Paul; Langer, Corey; Kalhan, Ravi; Patel, Jyoti; Schnoll, Robert
Abstract: Background: Continuing to smoke after a cancer diagnosis can adversely influence the prognosis for patients with cancer. However, remarkably few studies have carefully examined the use of first‐line FDA‐approved medications for nicotine dependence in patients with cancer. This study evaluated the feasibility, safety, and effect on cessation of varenicline for smoking cessation in patients with cancer. Methods: Data from 132 treatment‐seeking smokers who received 12 weeks of open‐label varenicline and five brief behavioral counseling sessions were used to evaluate the feasibility, safety, and impact on cessation of varenicline. The effects of abstinence on cognitive function and affect were also explored. Results: Of 459 patients screened, 306 were eligible for the study (66.7%) and 132 entered treatment (43.1%). Retention was 84.1% over 12 weeks. The rate of biochemically verified abstinence at week 12 was 40.2%. Expected side effects were reported (e.g. sleep problems, nausea), but there were no reports of elevated depressed mood, suicidal thoughts, or cardiovascular events. Abstinence was associated with improved cognitive function and reduced negative affect over time ( p  < 0.05). Conclusions: Although many patients with cancer who smoke did not enroll in treatment, the side effect profile of varenicline and its effect on short‐term cessation converge with what is seen in the general population. Further, as with the general population, abstinence while taking varenicline may lead to improved cognitive function and reduced negative affect. The present data support the use of varenicline to help patients with cancer to quit smoking.